(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aim & Background -The versatility in HR practices includes activities that generally include overall jobs and community, incentive-based compensation, organizational performance, widespread employee engagement, and Employee skills flexibility. HR practice flexibility plays an important role in management practice. However, evidence of its practice shows that there are impacts on the employee performance and creativity of the individual within the organization. This study investigates the role of Idea Generation and Employee Behavioral flexibility in determining the effects and relations between HR practice flexibility and Employee skills flexibility. Methods: The present study was accomplished in all colleges in Erbil Polytechnic University (EPU). The survey was based on paper and included questionnaires from all the selected colleges in the EPU. After 2 weeks we have given reminder to the Colleges who had not yet responded. So after 3 weeks a total of 127 usable questionnaires were returned to us from the EPU. Hypotheses were tested and analyzed statistically using SPSS software. Results - findings show the relationship between the independent variable (HR) and the mediating variable (EBF) was significant because the value of (PV), this indicates the existence of a positive significant relationship between the independent variable and the dependent variable. The modified variable (IG) has a positive role and modifies the positive significant relationship (the P. value of the regression weight is the lowest level of statistical significance, between the independent variable (HR) and the mediator variable (EBF) at the higher levels of the variable values. We note also that the modified variable mentioned above and at low levels does not modify the relationship between the independent and mediating variables, but rather makes it insignificant, that is, the absence of the rate variable at lower levels is better compared to its presence at higher levels. Research limitations– the research limit the generalizability of the findings because the data collected in Erbil Polytechnic University (EPU). And each college has its own unique environment. Future studies can extend these findings by conducting studies in other societal contexts.